Penerapan Data Mining Dalam Menentukan Tingkat Kepuasan Orangtua Terhadap Kinerja Guru Pada Masa Pandemi Covid-19 : (Studi Kasus: SD Min Bahkapul Pematangsiantar) - Priya Adhitia; Riki Winanjaya (Politeknik Kampar, 2024)
The purpose of the study was to determine parental satisfaction with teacher performance during the COVID-19 pandemic. By knowing the level of parental satisfaction, the Elementary School can improve the quality of learning if it is not good and further improve teacher performance if the level of satisfaction is good. The method used in this study is the C4.5 Algorithm, where the data source used is a questionnaire/ questionnaire technique given to parents of students at SD MIN Bahkapul Pematangsiantar. The variables used include (1) Tangibles, (2) Reliability, (3) Responsive, (4) Assurance and (5) Empathy. The research test process usses RapidMiner software to create a decision tree. From the resultss of the analysis, it is hoped that it can improve the performance of SD MIN Bahkapul teachers so that the services provided to students can be even better.